Coinheritance Studies of Yield and Yield Related Traits in Wheat (Triticum Aestivum L.) Preliminary Lines - Mahnoor; Abdur Rauf; Ayesha; Suhail, Aamir; Nida Gulal; Khan, Anwar Hussain; Bibi, Hafsa; Rahid, Nazli; Khalid, Laila; Asma, Asma; Naz, Amna; Saleem, Sumbal; et al. (Indus Journal of Bioscience Research, 2024)
A field trial was performed to explore the genetic diversity and coheritability among the 64 bread wheat genotypes. These lines/genotypes were analyzed for days to heading, days to maturity, plant height, flag leaf area, spikelet Spike-1, grain per spike, thousand-grain weight, and grain yield. Based on the mean performance, the best genotype for early maturity was CCRIA1-10, CCRIA1-1, and CCRIA1-11. Likewise, for the flag leaf area, desirable genotypes were CCRIA1-16 and CCRIA1-27, and for grain spike-1, CCRIA1-28 and CCRIA1-22. In addition, the best genotypes for 1000-grain weight were CCRIA1-64 and CCRIA1-37. The highest genotypic and phenotypic coefficients of variation (PCV = 1054.40%, GCV = 446.68%) were recorded for grain yield, followed by grain spike-1 (PCV = 125.29 and GCV = 123.39). The highest heritability (0.97) was indicated by spike weight and grains spike-1(0.97), while plant height (0.58), 1000 grain weight (0.44), and flag leaf area (0.31) showed moderate heritability. The lowest heritability estimates were recorded for the length of the peduncle (0.01), length of spikes (0.13), grain yield (0.18), days to heading, and spikelet spike-1 (0.25). High coheritability was observed among day to maturity and spike weight (0.99), on the contrary, minimum coheritability was observed for the flag leaf area with heading (0.12). The most desired inheriting pairs were spikelet spike-1 with grains spike-1 (0.97), weight of spike with spikelet spike-1(0.92), and flag leaf area with spike weight (0.86), spike length with grains spike-1, spike weight with grains spike-1 and flag leaf area with grains spike-1.